Identification of desertified and preserved areas in a conservation unit in the state of Paraíba – Brazil - Leandro F. da Silva; Bartolomeu I. de Souza; Rafael Cámara Artigas (Cuadernos de Investigación Geográfica, 2022)
The objective of this study is to identify and analyse the main characteristics of areas potentially degraded by desertification and of preserved areas using the Soil Surface Moisture Index (SSMI), alongside the Land Surface Temperature (LST) and Normalized Difference Vegetation Index (NDVI). The study is based on a set of points obtained in the field and from the RGB false colour image for the Environmental Protection Areas (EPA) of the Cariri, in the semi-arid region of Paraíba, using a space-time cross-section covering both rainy and dry periods. The results showed that at all points in Desertified Areas, the main characteristics were a low SSMI, high LST and low NDVI in both periods. The Preserved Areas, on the other hand, presented a high SSMI, moderate LST and high NDVI in the rainy period, with the same characteristics repeated in the dry period for SSMI and NDVI, but with a low LST. Timely identification of these characteristics, both in areas degraded by desertification and in better preserved areas, can provide useful information for future decisions relating to the physical and territorial management of the Conservation Unit.